2008
DOI: 10.1111/j.1440-1789.2008.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Portal‐systemic shunt encephalopathy presenting with diffuse cerebral white matter lesion: An autopsy case

Abstract: We report herein an autopsy case of portal-systemic encephalopathy (PSE) presenting with diffuse tissue rarefaction in the cerebral deep white matter. Clinically, the patient showed recurrent episodes of unconsciousness, abnormal behavior and urinary incontinence, as well as flapping tremor. Cognitive impairment and peripheral neuropathy developed following recurrent episodes. Although conventional arterial portography revealed a small portal-systemic collateral vessel of a left gastro-renal venous shunt, abdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…In parallel, astrocytic reactivity may be a defense mechanism to modulate brain homeostasis by increasing astrocytic workload, and it may contribute to the elevation of brain pressure due to increased cellular volume. This process has been described in several cerebral diseases, including experimental and human HE (Pilbeam et al, 1983;Kimura et al, 2008). In this manuscript, we describe severe astrocytic morphological changes that characterize a state of diffuse astrocytic reactivity.…”
Section: Discussionmentioning
confidence: 85%
“…In parallel, astrocytic reactivity may be a defense mechanism to modulate brain homeostasis by increasing astrocytic workload, and it may contribute to the elevation of brain pressure due to increased cellular volume. This process has been described in several cerebral diseases, including experimental and human HE (Pilbeam et al, 1983;Kimura et al, 2008). In this manuscript, we describe severe astrocytic morphological changes that characterize a state of diffuse astrocytic reactivity.…”
Section: Discussionmentioning
confidence: 85%
“…Several studies used Doppler ultrasound imaging and scintigraphy to measure shunt rate and size, with many reporting the PSS to be ‘large’ or with a diameter ranging from 0·2 to 5 cm. It has been suggested that encephalopathy is not associated with PSSs, even in patients with cirrhotic livers, if the shunted fraction is less than 24–30 per cent.…”
Section: Discussionmentioning
confidence: 99%
“…Πλην της αρχετυπικής εκδήλωσης της φλοιοβασικής εκφύλισης με φαινότυπο φλοιοβασικού συνδρόμου, ήδη από πολλών ετών είχαν αναγνωρισθεί και άλλες εκδηλώσεις του νοσήματος, όπως με προεξάρχουσα άνοια ή αφασία 119,120 , με προοδευτική μείωση του παραγόμενου λόγου και στοματοπροσωπική δυσπραξία 121 , ως πρωτοπαθής προϊούσα αφασία, συνηθέστερα με τη μορφή μη ρέουσας αγραμματικής μορφής 122,123 , αλλά και ως αφασία αγωγιμότητας, με προεξάρχουσα δυσκολία στην επανάληψη 124 . Επίσης έχει αναφερθεί εκδήλωση ως οπίσθια φλοιώδης ατροφία, με οφθαλμοκινητική απραξία, οπτική αταξία και ταυτοχροναγνωσία 125 .…”
Section: διαγνωστικά κριτήριαunclassified